Small Medium Enterprises (SMEs) business owner’s wellbeing and business growth in Malaysia - Engku Aiesyah Amirah Engku Md Azmi, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The most common attribute found among successful Small Medium Enterprises (SMEs) is constantly growing their business. Business owner’s wellbeing evidently played pivotal role in SMEs business growth. Although extensive research has been carried out on the subject of SMEs business growth, their wellbeing remained relatively under-explored. As a result, a thorough understanding on SMEs business owner’s wellbeing in Terengganu was very poor and the barriers to business growth remain persistent. It is against this backdrop that this paper seeks to explore SMEs business owner’s attitude which impede their business growth that directly linked with their wellbeing. Analysis of data from 30 semi-structured interviews with SMEs related experts and business owners revealed six common traits of business owners’ attitude; complacent, reliance, expectation, inculpate, unmotivated and incurious. In addition to common traits, findings revealed further understanding on their attitudinal motivations. Thorough understanding on SMEs business owner’s attitude found among participants in this study explained their minimal growth which lies beyond superficial negative attribute that was projected, rather, driven by external circumstances. This study provides a fine-grained understanding of SMEs business owner’s wellbeing in Terengganu through a lenses of both experts and business owners.